(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
The article is part of a thesis research addressed the understanding of the specificity of historical knowledge through the use of historical sources in the teaching and learning processes of the discipline, with the objectives of making visible the representations of students that hindered the approach of the Spanish conquest of America, while recognizing the skills that would allow us to understand and interpret historical sources. Describes an action research in the chair of American History I of the First Cycle of History degrees, Faculty of Humanities and Sciences, National University of the Litoral. The choice of an action research proposal facilitated the approach to classroom situations experienced as problematic and required reflection-in-action on aspects concerning university teaching practices, such as social practices that are configured by considering the particularities, the heterogeneities and difficulties that the learning subjects have.